STRATEGI ADAPTASI PETANI MISKIN DALAM PENGELOLAAN LAHAN PERTANIAN DI PEDESAAN SUMATERA BARAT (Studi Kasus Masyarakat Nagari Sungai Tanang) - Dr. Erwin, M.Si Dr. Erwin, M.Si (Sosio Konsepsia, 2010)
This articel studies about the change of social economic function and the dynamic of land management in nuclearfamily at rural areas in West Sumatera. In Nagari Sungai Tanang, the increasi of population threats the existence of inherited wealth which caused the change of structure from matrilineal extended family to nuclear family. The research use qualitative approach, data was analysed by emic approach and etics analyse was conducted to formulate the research conclution and hypothesis compilation. The massiveness of land pawning coused by economical factors and land fragmentation caused by demographical pressures. The structure change of land ownership from communal to individual caused the function of social economic of matrilineal extended family, it cause the protection to old people, orphan and widow become less. The strategy of matrilineal nuclear family in fulfilling the life needs as a result from interaction between the rareness of fram land and developing market, which is structure in producting organization in the farm land; the movement from profit sharing system to the rental system; intensification and diservication of farm land use. Tights relation of right and obligation in consanguinity system and reciprocal exchange among individual in society start to become weaker and smaller together. To the group of society, that stage result in the decrease of social security in quantity and quality. The change at the level infra-structure caused the change of family structure and the structure of land ownership, but it doesn't influence to the supra structure level. The ideology of matrilineal system still remain concepted, althought there' the change at the level of infra-structure and structure, the society of Sungai Tanang stay remains to the Islam and custom rules.